Cultura Nambiquara em transformação : as perspectivas de estudantes indígenas em escolas não indígenas (Comodoro-MT) - Pinheiro, Francisco Clébio (2025)
Throughout history, indigenous peoples have endured centuries of invisibility and cultural silencing. This research emerges as an effort to shed light on central aspects of indigenous themes, affirming the need to rethink educational practices that still reflect this long trajectory of silence and neglect. It is necessary to create spaces where indigenous peoples can express their perspectives on their own culture and interactions with non-indigenous individuals. In this regard, the objective is to analyze the perceptions of young Nambiquara indigenous students who move from their villages to study in non-indigenous schools in the municipality of Comodoro-MT, investigating the cultural transformations resulting from this interculturality and the impact of the use of new technologies on their daily lives. It seeks to identify cultural continuities, manifested in ceremonies and others rituals, as well as the transformations generated by these interactions. The adopted methodology included bibliographic sources, oral history with attentive listening to the young indigenous students, and ethnography based on the accounts that reveal their impressions and experiences in the intercultural context. Among the expected results, the valorization of the traditional practices of the Nambiquara indigenous people stands out, sustained through the use of their native language, and the effort to reconcile technological elements with the experience of cultural heritage while also recognizing the transformations occurring in this process.This research contributes to broadening the debate on interculturality by highlighting the reflections of this interactions for the Nambiquara. Furthermore, it fosters reflections on the influence of new technologies and the school environment on indigenous identities. The relevance of this discussion is justified by the fact that, although current educational legislation values the inclusion of indigenous themes in schools, students’ perceptions reveal that it is still necessary to advanced so that they feel effectively included in these actions. For this, the schools needs to be an open space for dialogue, otherness and paradigm shift, in order to understand the multiple forms of living in society.